The Implementation of Local Cultural Values in the Government System of Nagari Sungai Sariak - Ilham, Muhammad; Frinaldi, Aldri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research, entitled “The Implementation of Local Cultural Values in the Government System of Nagari Sungai Sariak,” is motivated by the diminishing application of Minangkabau cultural values in the administration of nagari governance. The purpose of this study is to examine how local cultural values are applied within the governmental system of the nagari and to identify the factors contributing to the decline of these values in practice. This study uses a qualitative approach with a simple research design. Data were collected through interviews, direct observation, and document analysis involving the Wali Nagari, the Kerapatan Adat Nagari (KAN), the Badan Musyawarah (BAMUS), and community leaders in Nagari Sungai Sariak, VII Koto District, Padang Pariaman Regency. The results of the study show that the implementation of Minangkabau cultural values consisting of egalitarianism, competitiveness, togetherness, careful consideration, deliberation and consensus, and adaptability remains present in the nagari government system but has not been fully realized. Values such as equality and togetherness have begun to decline due to the influence of a hierarchical modern bureaucratic system. Moral consideration and deliberation have also weakened as traditional institutions lose their role in decision-making processes. Meanwhile, the value of adaptability has begun to be applied through the use of technology, although it is not yet balanced with the reinforcement of traditional and cultural values. Overall, the study indicates that the nagari government continues to make efforts to preserve Minangkabau cultural values despite the ongoing challenges of modernization